Deciphering the mRNP Code: RNA-Bound Determinants of Post-Transcriptional Gene Regulation. Issue 5 (May 2017) - Gehring, Niels H.; Wahle, Elmar; Fischer, Utz
Abstract : Eukaryotic cells determine the final protein output of their genetic program not only by controlling transcription but also by regulating the localization, translation and turnover rates of their mRNAs. Ultimately, the fate of any given mRNA is determined by the ensemble of all associated RNA-binding proteins (RBPs), non-coding RNAs and metabolites collectively known as the messenger ribonucleoprotein particle (mRNP). Although many mRNA-associated factors have been identified over the past years, little is known about the composition of individual mRNPs and the cooperation of their constituents. In this review we discuss recent progress that has been made on how this 'mRNP code' is established on individual transcripts and how it is interpreted during gene expression in eukaryotic cells. Trends: The mRNA-bound proteome is more complex than previously anticipated and comprises up to 1000 RBPs. Because there are many mRNA-interacting factors, and each mRNA is the blueprint of a particular protein, the resulting ribonucleoprotein particles (mRNPs) are likely to be unique in their composition. The 'mRNP code' concept implies that specific sets of proteins, non-coding RNAs, and other molecules bind to individual mRNAs and control their fate and function in every cell. The mRNP code is highly dynamic and reflects the functional status of each mRNA. Previously unknown RNA-binding domains show unconventional modes of RNA–protein interactions. Recent technologies such as high-throughput analyses of RNA–protein interactions and ribosome profiling have revealed binding sites and sequences of multiple RBPs in vivo and in vitro .